1998
DOI: 10.6028/nist.ir.6091
|View full text |Cite
|
Sign up to set email alerts
|

Recertification of the SRM 706a, a polystyrene

Abstract: Certain commercial materials and equipment are identified in this paper in order to specify adequately the experimental procedure. In no case does such identification imply recommendation or endorsement by the National Institute of Standards and Technology, nor does it imply necessarily the best available for the purpose. According to ISO 31-8, the term "Molecular Weight" has been replaced by "Relative Molecular Mass," symbol M r Thus, if this nomenclature and notation were followed in this publication, one sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2001
2001

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This preliminary comparison showed that polymer samples taken from all the vials produced identical chromatograms. A statistical analysis using methods of comparing chromatograms used in this laboratory for looking at bottle-to-bottle variation of NIST standard reference materials (SRMs) confirmed these observations . Details of that work are to be published as a NISTIR…”
Section: Preparation Of Materials and Homogeneity Testingmentioning
confidence: 99%
“…This preliminary comparison showed that polymer samples taken from all the vials produced identical chromatograms. A statistical analysis using methods of comparing chromatograms used in this laboratory for looking at bottle-to-bottle variation of NIST standard reference materials (SRMs) confirmed these observations . Details of that work are to be published as a NISTIR…”
Section: Preparation Of Materials and Homogeneity Testingmentioning
confidence: 99%
“…For this purpose, we employ a scheme similar to that used in ref. [29] for the estimation of systematic uncertainties in SRM's 1482, 1483 and 1484 and ref [31] on the recertification of SRM 706a. These uncertainties are listed in Table 2 for SRM 2887.…”
Section: Estimation Of Uncertainties Due To Systematic Effects In Thementioning
confidence: 99%
“…(15) The coefficients in eq. (16) are related to the M w , molecular mean-square radius of gyration, R G 2 , the second viral coefficients, A 2 , and the third virial coefficients, A 3 , by [28,29]:…”
Section: Analysis Of Light Scattering Datamentioning
confidence: 99%
“…For this purpose, we employ a scheme similar to that used in ref. [28] for the estimation of systematic uncertainties in SRM's 1482, 1483 and 1484 and ref [29] on the recertification of SRM 706a. These uncertainties are listed in Table 2 for SRM 2885.…”
Section: Estimation Of Uncertainties Due To Systematic Effects In Thementioning
confidence: 99%